Quality management system and accreditation of measurements in a surface science laboratory: the case study of MiNALab1. (2nd May 2014) - Iacob, Erica; Vanzetti, Lia; Gennaro, Salvatore; Pecoraro, Federico; Giubertoni, Damiano; Barozzi, Mario; Bortolotti, Mauro; Pepponi, Giancarlo; Fedrizzi, Michele; Bersani, Massimo; Abel, Marie‐Laure; Rossi, Antonella; et al.
<x xml:space="preserve">Abstract</x> With the continuously increasing demand for traceable and often accredited measurements in the scientific community, the quality management of laboratory activity according to international ISO standards can be a valuable and proficient solution. In this paper, we describe a decade of work in this direction. The implementation of quality management according to the ISO/IEC 17025 'General requirements for the competence of testing and calibration laboratories' in a surface science research‐oriented analytical laboratory is presented. We analyze difficulties and drawbacks as well as benefits and permanent improvements that followed the accreditation, its maintenance, and extension to new methods. Copyright © 2014 John Wiley & Sons, Ltd.